A nullimorphic ERLIN2 mutation defines a complicated hereditary spastic paraplegia locus (SPG18) - Alazami, Anas M. (Springer-Verlag, 2011)
Hereditary Spastic Paraplegia (HSP) is a clinically and genetically heterogeneous group of neurological disorders that are characterized by progressive spasticity of the lower extremities. We describe an extended consanguineous Saudi family in which HSP is linked to SPG18, a previously reported autosomal recessive locus, and show that it is associated with a nullimorphic deletion of ERLIN2, a component of endoplasmic reticulum associated degradation. This finding adds to the growing diversity of cellular functions that are now known to be involved in the maintenance of the corticospinal tract neurons.